A comparison of the physiological responses to exercise on five different upper and lower body ergometers - Spranger, L. L. (1998)
The purpose of this investigation was to compare VO2, HR, RER, RPE, Kcals, and O2 pulse to exercise at a self-selected submaximal intensity on an air walker (ST), an elliptical exerciser (ELLP), a cross-country skiing simulator (XC), a nonmotorized treadmill (WALK), and an Airdyne bicycle (AD). Ten female college-aged volunteers exercised for 30 minutes at a self-selected pace on each modality on separate days, in random order. VO2 for ST was 31.4, for ELLP was 34.6, for XC was 29.2(a), for WALK was 32.7, and for AD was 30.5(a). Kcals/min for ST were 9.9, for ELLP were 10.9, for XC were 9.2a, for WALK were 9.9, and for AD were 9.6(a). HR for ST was 170, for ELLP was 172, for XC was 162(a), for WALK was 166, and for AD was 167. RER for ST was 0.97, for ELLP was 0.99, for XC was 0.97, for WALK was 0.96, and for AD was 0.98. RPE for ST was 13.0, for ELLP was 12.6, for XC was 12.2, for WALK was 11.6(a), and for AD was 12.5. O2 Pulse for ST was 11.7(a,b), for ELLP was 12.8, for XC was 11.4(a,b), for WALK was 12.5, and for AD was 11.5(a,b); (a= significantly different than ELLP, b = significantly different than WALK). In general, responses to WALK and ELLP were greater than ST, XC, and AD, respectively. When comparing WALK to ELLP, O2 Pulse values were similar, but since WALK values were achieved at a lower RPE (11.6 vs. 12.6) exercising on the WALK may be the most beneficial exercise mode for maximizing energy expenditure while exercising at self-selected, moderate intensities. (1998. M.S., University of Wisconsin-La Crosse (John Porcari). (34pp 1f $5.00) PH 1643, vol. 12,1)